2000
DOI: 10.1007/s100670050037
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Entire Spinal Cord and Medulla Oblongata in Acute Catastrophic-Onset Transverse Myelitis in SLE

Abstract: A 30-year-old Caucasian male with systemic lupus erythematosus suffered acute catastrophic-onset transverse myelitis. Two years earlier aseptic meningitis, another rare CNS lupus manifestation, had been diagnosed. MRI showed involvement of the medulla oblongata and the entire spinal cord. Therapy with intravenous high-dose methylprednisolone and intravenous cyclophosphamide is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 6 publications
1
15
0
2
Order By: Relevance
“…Based on her long history of SLE, and clinical symptoms, and the lack of findings of microorganism infection, no intoxica- tion to penicillins and no oligoclonal band in CSF, these findings were considered to be compatible with previous reports of SLE-related transverse myelitis (4)(5)(6)(7)(8)(9). Symptoms and physiological findings in the present case; urinary and rectal dysfunction, facial nerve palsy, medial longitudinal fascicular syndrome, numbness of the left limb and bilateral upper extremities, deficiency of all sensation of right limb, and tetraplegia were relatively compatible with the visualized longitudinal spinal lesions of this disorder on MRIassessments.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Based on her long history of SLE, and clinical symptoms, and the lack of findings of microorganism infection, no intoxica- tion to penicillins and no oligoclonal band in CSF, these findings were considered to be compatible with previous reports of SLE-related transverse myelitis (4)(5)(6)(7)(8)(9). Symptoms and physiological findings in the present case; urinary and rectal dysfunction, facial nerve palsy, medial longitudinal fascicular syndrome, numbness of the left limb and bilateral upper extremities, deficiency of all sensation of right limb, and tetraplegia were relatively compatible with the visualized longitudinal spinal lesions of this disorder on MRIassessments.…”
Section: Discussionsupporting
confidence: 80%
“…In their analysis, more aggressive treatment was not necessarilly associated with better outcome. Lack of response to the intensive treatments in the present case may be due to the relatively narrow therapeutic window in the case of acute onset (8). Magneticresonance angiographic findings of diffuse stenotic lesions in cerebral arteries and laboratory data presenting secondary fibrinolysis accompanied with accelerated coagulation cascade suggested that any vasculopathy in addition to the autoimmunepathogenesis may have been related to the acute development of longitudinal transverse myelitis in the present refractory case.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In general, ATM-MS tends to be incomplete and restricted to a single spinal segment, whereas ATM in association with viral infections or other inflammatory conditions of the spinal cord more often extends beyond two or more spinal levels [46,59,65,67,68]. As a result, clinical impairment is usually more severe than that associated with ATM-MS [46,75,76]. In accordance with these studies, monosegmental involvement of the spinal cord was most frequent in ATM-MS.…”
Section: Discussionmentioning
confidence: 99%
“…Kovacs et al determined that TM was the initial manifestation in 39 % of SLE patients and it presented in the first 5 years [24]. The prognosis is generally poor and depends on such factors as rapidity of diagnosis, extent of spinal cord involvement, and prompt treatment with high-dose corticosteroids, and pulse cyclophosphamide [25,28]. There are also case reports of pSS with acute transverse myelopathy as the initial manifestation [12,13].…”
Section: No Follow-up At the Time Of Writingmentioning
confidence: 97%